A Comparative Study of Marx’s Perceptual View of Nature and Hegel’s Philosophy of Nature - Wang, Xiaotong (Transactions on Social Science, Education and Humanities Research, 2023)
Marx’s perceptual view of nature is a positive rejection of Hegel’s philosophy of nature, which retains the positive parts of Hegel’s dialectic and rejects the shortcomings of objective idealism. At its root, Marx recognized the nature externalized by Hegel on the basis of abstract thought as "nothing", thus launching a critique of Hegel’s natural philosophy. In the process of criticizing Hegel’s natural philosophy, Marx combined nature with real and historical sensual activities, and with the dialectics of nature, showing the view of nature under the new worldview.